(untitled) (International journal of medical sciences, 2026)
Chronic cholecystopancreatitis is a combined inflammatory condition involving both the gallbladder and the pancreas. It usually develops as a result of long-standing gallstone disease, chronic biliary obstruction, or recurrent episodes of acute inflammation. The anatomical and functional relationship between the biliary tract and pancreas explains the frequent coexistence of these pathologies. This article reviews the etiology, pathogenesis, clinical manifestations, diagnostic methods, and management strategies.